Perancangan Fasilitas Duduk Berbasis Pengaplikasian Keramik - Aaron Aristo Notohutomo; Adi Santosa; Celine Junica Pradjonggo (Intra, 2018)
This interior furniture design based on ceramic material application aims to optimize the basic nature of pottery when applied to the elements of seating facility. Ceramic natural characteristic which is fragile will be overcome by process of material shape. The application of other materials combination as to accomplish seating facility design which is worthy to be marketed. This design is a development of a prototype previously made by designer himself. The method used consists of understanding the nature of ceramic, making the concept of problem solving, prototype, and branding. The result of this design is 3 sets of seating facility design and 1 set of prototype. Ceramic material can be applied to the sitting facility while maintaining its original properties. This design has a chance to be developed further.